„Racz nam wrócić, Panie...” - Siwicka, Dorota (Załącznik Kulturoznawczy, 2023)
The article entitled Racz nam wrócić, Panie... (Give us back, Lord…) is a reconstruction of the social history (from the 19th century to modern times) of Polish patriotic-religious song Boże coś Polskę (God save Poland), and especially one of its lines that is known and sang in two different versions: ‘Lord bless our free homeland’ and ‘Lord give us a free homeland back’. This small difference between the versions is interpreted by the author in a Derrida style: as a shibboleth – a test of the identity of people singing this song, a password of a secret association and a sign allowing the recognition of a friend from foe. At the same time she points to the permanence of the significant function that is fulfilled in the Polish patriotic ritual by the singing of God save Poland